2020
DOI: 10.1002/adma.202002564
|View full text |Cite
|
Sign up to set email alerts
|

Multimode Hydraulically Amplified Electrostatic Actuators for Wearable Haptics

Abstract: The sense of touch is underused in today’s virtual reality systems due to lack of wearable, soft, mm‐scale transducers to generate dynamic mechanical stimulus on the skin. Extremely thin actuators combining both high force and large displacement are a long‐standing challenge in soft actuators. Sub‐mm thick flexible hydraulically amplified electrostatic actuators are reported here, capable of both out‐of‐plane and in‐plane motion, providing normal and shear forces to the user’s fingertip, hand, or arm. Each act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
188
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 39 publications
(42 reference statements)
0
188
2
Order By: Relevance
“…The surface texture, topography, stiffness, deformation, applied force, and other desired information of the internal organs of the patient can be measured and fed back by the integrated sensing system of the surgical tools and then transmitted to the surgeon through tactile reproduction provided by the soft actuator array. Some researches using soft robotic technologies for haptic feedback have emerged in recent years, and a recent review of them can be found in the study by Yin et al [408] Common haptic feedback methods based on mechanical stimulation include vibrotactile stimulation, [409,410] normal pressing, [411,412] and skin stretch, [413,414] and the introduction of soft technologies can achieve safe, compact, and lightweight system integration as well as good simulation of tactile sensation of soft organs.…”
Section: Robotic Assistancementioning
confidence: 99%
“…The surface texture, topography, stiffness, deformation, applied force, and other desired information of the internal organs of the patient can be measured and fed back by the integrated sensing system of the surgical tools and then transmitted to the surgeon through tactile reproduction provided by the soft actuator array. Some researches using soft robotic technologies for haptic feedback have emerged in recent years, and a recent review of them can be found in the study by Yin et al [408] Common haptic feedback methods based on mechanical stimulation include vibrotactile stimulation, [409,410] normal pressing, [411,412] and skin stretch, [413,414] and the introduction of soft technologies can achieve safe, compact, and lightweight system integration as well as good simulation of tactile sensation of soft organs.…”
Section: Robotic Assistancementioning
confidence: 99%
“…[ 17,18 ] Yet, DEAs require high driving voltages in the kilovolts range and suffer from dielectric breakdowns, which irreversibly damage the lens (Table S1, Supporting Information). Actuators based on the displacement of dielectric liquids via zipping electroactive polymers (ZEAP) survive dielectric breakdown and have promising applications as artificial muscles for soft robotics [ 19,20 ] and wearable haptic displays, [ 21 ] but they require high driving voltages as well.…”
Section: Figurementioning
confidence: 99%
“…Omitting this connection can lead to directional inflation of the membrane, which is beneficial for other applications that involve touch, such as buttons or brail displays. [ 21 ] Heat‐sealing the electrodes in regular steps along the edge of the electrodes introduces specific starting points for zipping to improve the zipping homogeneity (we use this for all our lenses) and partially reduces the threshold voltage (Figure S3, Supporting Information). The dielectric fluid is a low viscosity paraffin oil with a refractive index n = 1.48 (close to PDMS); it is injected with a syringe through an access tube and sealed.…”
Section: Figurementioning
confidence: 99%
“…[ 28–30 ] This actuation strategy, which so far has been demonstrated for miniature (up to a few millimeters) tactile interfaces with displacements lower than 1 mm, might be challenged for higher displacements by the need for a larger lateral size, due to the zipping effect required for pressurization. [ 29,30 ]…”
Section: Introductionmentioning
confidence: 99%